The Effect of Resilience on Student Psychological Distress During Pandemic - Khotimah, Khusnul; Panggabean, Aninda Namira; Ardianti, Tiara (Universitas Muhammadiyah Metro, 2021)
The COVID-19 pandemic has forced students to obey government regulations to conduct online lectures. It is not uncommon for students to feel stressed due to the many demands of lectures and worry about being infected with the virus. This study aims to determine the extent of the effect of resilience on students' psychological distress during the pandemic. The data collection technique is non-empirical and is carried out online and offline. The research subjects were 200 active students pursuing undergraduate education in Malang. The results showed a negative effect between resilience and student psychological distress during the pandemic. Psychological distress in students is dangerous if it is not resolved immediately. The importance of resilience will significantly help students prevent or overcome the stress that occurs primarily during the pandemic. The advantage of this research is that it relates to most students who feel stressed so that it can become new knowledge for students or other readers.Keywords: resilience; psychological distress; the covid-19 pandemicAbstrakPandemi covid-19 memaksa mahasiswa untuk menaati peraturan pemerintah untuk melaksanakan perkuliahan secara daring. Tidak jarang mahasiswa merasa stres akibat banyaknya tuntutan perkuliahan dan khawatir akan tertulas virus. Penelitian ini bertujuan untuk mengetahui sejauh mana pengaruh resiliensi terhadap distress psikologis mahasiswa di masa pandemi. Teknik pengumpulan data yaitu non empirik, yang dilakukan dengan cara daring dan luring. Subjek penelitian sejumlah 200 mahasiswa aktif yang menempuh pendidikan S1 di Malang. Hasil penelitian menunjukkan bahwa ada pengaruh negatif antara resiliensi terhadap distress psikologis mahasiswa di masa pandemi. Distress psikologis pada mahasiswa merupakan hal yang berbahaya jika tidak segera diselesaikan. Pentingnya resiliensi akan sangat membantu mahasiswa untuk mencegah ataupun mengatasi stres yang terjadi terutama di masa pandemi. Kelebihan dari penelitian ini yaitu sangat relate dengan kebanyakan mahasiswa yang merasa stress, sehingga dapat menjadi pengetahuan baru bagi mahasiswa atau pembaca lainnya.Kata kunci: resiliensi; distress psikologis; pandemi covid-19